2019 Focused Update of the Guidelines of the Taiwan Society of Cardiology for the Diagnosis and Treatment of Heart Failure - Wang, Chun-Chieh (Acta Cardiol Sin, 2019)
Heart failure is a growing epidemic, especially in Taiwan because of the aging population. The 2016 Taiwan Society of Cardiology – Heart Failure with reduced Ejection Fraction (TSOC-HFrEF) registry showed that the guideline-recommended therapies were prescribed suboptimally both at the time of hospital discharge and during follow-up. We, therefore, conducted this 2019 focused update of the guidelines of the Taiwan Society of Cardiology for the diagnosis and treatment of heart failure to reinforce the importance of new diagnostic and therapeutic modalities of heart failure. The 2019 focused update discusses new diagnostic criteria, pharmacotherapy, non-pharmacological management, and certain co-morbidities of heart failure. Angiotensin receptor neprilysin inhibitor and If channel inhibitor is introduced as new and recommended medical therapies. Latest criteria of cardiac resynchronization therapy, implantable cardioverter-defibrillator, heart transplantation, and ventricular assist device therapy are reviewed in the non-pharmacological management chapter. Co-morbidities in heart failure are discussed including chronic kidney disease, diabetes, chronic obstructive pulmonary disease, and sleep-disordered breathing. We also explain the adequate use of oxygen therapy and non-invasive ventilation in heart failure management. A particular chapter for chemotherapy-induced cardiac toxicity is incorporated in the focused update to emphasize the importance of its recognition and management. Lastly, implications from the TSOC-HFrEF registry and post-acute care of heart failure are discussed to highlight the importance of guideline-directed medical therapy and the benefits of multidisciplinary disease management programs. With guideline recommendations, we hope that the management of heart failure can be improved in our society.